The Right of Khiyar Ta’yin in the Sale and Purchase of Electronic Products Online at Shopee Marketplace - Makraja, Fahmi; Safrizal, Riyan Auliyanda; Al Fajri, Mirza; Fitriyani, Elya (Jurnal Iqtisaduna, 2025)
The right of khiyar that provides specific information related to similar products but different in quality is khiyar ta’yin. In practice, in purchasing electronic products on the Shopee marketplace, there are comments and testimonial columns that contain various consumer experiences related to electronic products that they have previously purchased, but many consumers who use testimonials and comments as a reference feel cheated in terms of product quality. This research uses a qualitative method and descriptive analysis approach. The author concludes that the implementation of khiyar ta’yin in the form of testimonial reviews and comments in purchasing electronic products on the Shopee marketplace is not fully in accordance with Islamic law. Because consumers do not use testimonials and comments as the main reference in purchasing electronic products because of doubts about the contents of testimonials and comments, information related to product quality and specifications provided in the form of testimonials and comments often contradict the actual facts of the goods that consumers have purchased so that this is financially detrimental to consumers, the time limit for khiyar ta’yin given by Shopee is 12 days from the time the product is shipped.